Prevalence of Maternal Postnatal Anxiety and Its Association With Demographic and Socioeconomic Factors: A Multicentre Study in Italy - Cena, Loredana; Gigantesco, Antonella; Mirabella, Fiorino; Palumbo, Gabriella; Trainini, Alice; Stefana, Alberto (Frontiers in Psychiatry, 2021)
Anxiety is a common perinatal disorder that can cause severe adverse consequences. This study (a) assesses the prevalence of maternal postnatal anxious symptomatology, and (b) analyses its association with demographic and socioeconomic variables as well as obstetric and other psychosocial variables. The assessment included 307 mothers aged ≥18 years with a biological baby aged ≤52 weeks and from seven Italian healthcare centres, evaluated using a Psychosocial and Clinical Assessment Form (also covering demographic and socioeconomic factors), and the state scale of the State-Trait Anxiety Inventory. We found an overall prevalence of self-reported postnatal anxious symptoms of 34.2%. More specifically, the prevalence was 34.5% at 1–24 weeks postpartum, and 30.8% at >24 weeks postpartum. No associations between postnatal anxious symptoms and demographic or socioeconomic variables were observed. As regards the other variables, the findings indicated antenatal depression or anxiety, parity and current psychological support from the partner as having the strongest relationships.